AN UNUSUAL COMBINATION OF SODOMY AND ASPHYXIA IN A YOUNG MALE, AN ARISING MATTER OF CONCERN IN THE CURRENT LAW (Journal of Forensic Medicine & Toxicology, 2022)
In India, heinous crimes like murder had been elevating in the recent past few years according to National Crime Record Bureau (NCRB). The gender comparison of murders that occurred in India concluded that males had topped the list. The capital city, New Delhi, had the highest number of murder victims among the 20 metropolitan cities. The authors report a case of a 24-year-old male, who was murdered by his own friend, and both were found to be following homosexual relationship. Hence a combination of chronic sodomy (male rape) and asphyxia is an infrequent presentation and rarely reported. It can be easily missed by Medical Officers lacking forensic knowledge and budding Forensic specialist at autopsy as the cause of death identified is unrelated to the finding. Considering the amendments related to rape laws, which is an arising issue there are high chances that these cases go unreported. Hence, the authors would like to put forward one such case to the literature, which can guide the Medical Officers lacking forensic knowledge and budding Forensic specialist.
Keywords: Homicide; Sodomy; Strangulation; Smothering